HMG CoA reductase expression as a prognostic factor in Korean patients with breast cancer: A retrospective study. Issue 13 (March 2019) - Kim, Hyojeong; Seol, Young Mi; Choi, Young Jin; Shin, Ho-Jin; Chung, Joo Seop; Shin, Nari; Kim, Ahrong; Kim, Jee Yeon; Kim, Keun Young; Bae, Youngtae
Abstract : Abstract: There are many preclinical and epidemiological reports suggesting a correlation between 3-hydroxy-3-methylglutaryl-coenzyme A reductase (HMG-CoAR) or HMG-CoAR inhibitor (statin) treatment and prognosis in breast cancer. This study aimed to investigate the expression of HMG-CoAR in Korean patients with breast cancer. The expression of HMG-CoAR on tissue microarrays from 191 patients who underwent resection from 2005 to 2006 in the Pusan National University Hospital was assessed by immunohistochemistry (IHC). The IHC assessment by a board-certified pathologist included areas of both carcinoma and peritumoral tissue of the breast. The scores of cancer-specific staining were adjusted by the scores of peritumoral staining. The patients were followed for a median 9.1 years. Disease-free survival (DFS) was shorter in patients with a positive adjusted HMG-CoAR score by log-rank test (not reached vs 11.6 years, P  = .011). After adjusting for age, T stage, N stage, pathological grade, perioperational chemotherapy, adjuvant radiotherapy, estrogen receptor positivity, progesterone receptor positivity, human epidermal growth factor receptor-2 positivity, and high Ki-67 (>10%), a positive adjusted HMG-CoAR IHC score was also associated with shorter DFS (hazard ratio = 2.638, 95% confidence interval [CI] 1.112–6.262, P  = .028). The expression of HMG-CoAR might be an independent prognostic factor in breast cancer. There are established drugs targeting HMG-CoAR, and further studies on its potential as a predictive marker are needed.